Safety and efficacy of opicinumab in patients with relapsing multiple sclerosis (SYNERGY): a randomised, placebo-controlled, phase 2 trial. Issue 9 (September 2019) - Cadavid, Diego; Mellion, Michelle; Hupperts, Raymond; Edwards, Keith R; Calabresi, Peter A; Drulović, Jelena; Giovannoni, Gavin; Hartung, Hans-Peter; Arnold, Douglas L; Fisher, Elizabeth; Rudick, Richard; Mi, Sha; et al.
Summary: Background: Opicinumab is a human monoclonal antibody against LINGO-1, an inhibitor of oligodendrocyte differentiation and axonal regeneration. Previous findings suggested that opicinumab treatment might enhance remyelination in patients with CNS demyelinating diseases. We aimed to assess the safety and efficacy of opicinumab in patients with relapsing multiple sclerosis. Methods: We did a randomised, double-blind, placebo-controlled, dose-ranging, phase 2 study (SYNERGY) at 72 sites in 12 countries. Participants (aged 18–58 years) with relapsing multiple sclerosis (relapsing-remitting multiple sclerosis and secondary progressive multiple sclerosis with relapses) were randomised in a 1:2:2:2:2 ratio by an interactive voice and web response system to opicinumab 3 mg/kg, 10 mg/kg, 30 mg/kg, or 100 mg/kg, or placebo. An identical volume of study drug was administered intravenously once every 4 weeks. All participants self-administered intramuscular interferon beta-1a as background anti-inflammatory treatment once a week. The primary endpoint was the percentage of participants achieving confirmed disability improvement over 72 weeks, which was a multicomponent endpoint measured by the Expanded Disability Status Scale, the Timed 25-Foot Walk, the Nine-Hole Peg Test, and the 3 s Paced Auditory Serial Addition Test. The primary endpoint was analysed under intention-to-treat principles. This study is registered atClinicalTrials.gov, numberNCT01864148 . Findings: Between Aug 13, 2013, and July 31, 2014, 419 patients were enrolled and randomly assigned either placebo (n=93) or opicinumab 3 mg/kg (n=45), 10 mg/kg (n=95), 30 mg/kg (n=94; one patient did not receive the assigned treatment), or 100 mg/kg (n=92). The last patient visit was on March 29, 2016. Confirmed disability improvement over 72 weeks was seen in 45 (49%) of 91 patients assigned to placebo, 21 (47%) of 45 assigned to opicinumab 3 mg/kg, 59 (63%) of 94 assigned to opicinumab 10 mg/kg, 59 (65%) of 91 assigned to opicinumab 30 mg/kg, and 36 (40%) of 91 assigned to opicinumab 100 mg/kg. A linear dose-response in the probability of confirmed disability improvement was not seen (linear trend test p=0·89). Adverse events occurred in 79 (85%) patients assigned placebo and in 275 (85%) assigned any dose of opicinumab. The most common adverse events of any grade in patients assigned any dose of opicinumab included influenza-like illness (140 [43%] with any dose of opicinumab vs 37 [40%] with placebo), multiple sclerosis relapses (117 [36%] vs 30 [32%]), and headache (51 [16%] vs 23 [25%]). Serious adverse events reported as related to treatment were urinary tract infection in one (1%) participant in the the placebo group, suicidal ideation and intentional overdose in one (1%) participant in the 30 mg/kg opicinumab group, bipolar disorder in one (1%) participant in the 100 mg/kg opicinumab group, and hypersensitivity in four (4%) participants in the 100 mg/kg opicinumab group. One patient in the opicinumab 30 mg/kg group died during the study due to a traffic accident, which was not considered related to study treatment. Interpretation: Our findings did not show a significant dose-linear improvement in disability compared with placebo in patients with relapsing multiple sclerosis. Further studies are needed to investigate whether some subpopulations identified in the study might benefit from opicinumab treatment at an optimum dose. Funding: Biogen.